Evaluation Practices: A Pertinent Reflection for Distance Education - Cifuentes Medina, José Eriberto (Rastros Rostros, 2014)
This study investigates the evaluative practices used in distance education. It employs a qualitativeapproach and a descriptive research method, and uses a stratified sample that was taken from thepopulation of distance education students at the Universidad Pedagógica y Tecnológica de Colombia.These students were given a survey to collect data and information, which was then systematized. Byexamining the results of a small sample, it was possible to ascertain the students’ opinions about thedistance education evaluation process in the non-degree programs of Pharmacy Management andHealth Management. Furthermore, a dissertation could be presented on distance education evaluationpractices that have incorporated Information and Communications Technology (ict), which, throughthe Moodle platform, offer a variety of instruments for measuring students’ learning
Keywords: instruments; distance; techniques; evaluation